Sally Ride : first American woman in space - Camp, Carole Ann. (Springfield, NJ : Enslow Publishers, 1997)
A biography of Sally Ride, who in 1983 became the first American woman to travel in space.
"Chronology": p. 97.
Includes bibliographical references (p. 102) and index.
Keywords: Ride, Sally -- Juvenile literature; Ride, Sally; Women astronauts -- United States -- Biography -- Juvenile literature; Astronauts -- United States -- Biography -- Juvenile literature; Astronauts; Women -- Biography